Dramaturgical Roles of Present and Past Teenage Characters in Post-Agreement Northern Irish Drama - Kurdi, Mária (Hungarian Journal of English and American Studies, 2022)
The Good Friday Agreement (1998) has set in motion significant changes in Northern Ireland, generating new conditions which, however, also brought numerous problems to the surface on various levels of society. Sociologists have called attention to how intensely the persistent afterlife of sectarian hostilities affect especially teenagers who are often unable to see their goals clearly. Several contemporary Northern Irish playwrights have relied on young characters to pinpoint timely and pressing social and cultural issues as well as to throw light on the precarity of the post-Troubles environment. This essay discusses three plays from different decades of the post-Agreement period: Gary Mitchell’s Trust (1999), Lucy Caldwell’s Leaves (2007), and Owen McCafferty’s Quietly (2012). Their respective dramaturgies showcase the long-lasting influence of the historical burden of the Northern Irish conflict on young peoples’ subjectivities as well as demonstrate how middle-aged characters are still haunted by memories of the psychic wounds they suffered during the most formative years of their lives. Through their underage protagonists, each playwright suggests that members of this generation might not be able to further strengthen the peace they have formally inherited. (MK)